Financial technology and disruptive innovation in ASEAN - Anshari, Muhammad, 1977-; Almunawar, Mohammad Nabil, 1960-; Masri, Masairol, 1974- (Advances in finance, accounting, and economics (AFAE) book series., 2020)
"This book examines new business models, applications, processes, products, or services with an associated material effect on financial markets and institutions and the provision of financial services"--